School Culture Transformation through Collaborative Leadership Practices - Kurniasih, Wina; Sururi, Sururi; Suryadi, Suryadi (JP (Jurnal Pendidikan) : Teori dan Praktik, 2025)
This study examines school culture transformation as a foundation for sustainable teacher professional development by analyzing how collaborative leadership shapes collaborative cultural practices in Indonesian elementary schools. Using a mixed-methods sequential exploratory design, data were collected from 298 teachers across 51 public schools in Purwakarta District and analyzed using Partial Least Squares Structural Equation Modeling. The findings show that collaborative leadership significantly predicts the development of a collaborative school culture, which subsequently enhances teacher professional growth and performance. The model explained about 30% of the variance in collaborative culture and 38% in teacher performance, with cultural transformation serving as a meaningful mediator between leadership and teacher outcomes. The study revealed that improvement occurred through cultivating mutual trust and a sense of safety, strengthening a common purpose and confidence in working together, and embedding routines that encourage reflective practice and collaboration among peers. The study concludes that collaborative leadership functions as a strategic driver for strengthening teacher development and advancing school culture transformation in Indonesia.